The Food Gap and Food Security of Poultry Meat in Saudi Arabia - Saied , Maha Abdel-Fattah; Elsebaei , Momtaz Nagy; Tawfik , Rady Talaat; Ameen, Faleh Abdelnaeem (Jordan Journal of Agricultural Sciences, 2022)
This research aimed to explore the current situation of the food gap and the food security of poultry meat in the Kingdom, based on secondary published data by the food and Agriculture Organization of the United Nations (FAO), the Ministry of Environment, Water and Agriculture, the General Authority for statistics, the Arab Organization for Agricultural Development (AOAD), and the international information Network. The results indicated a decline in self-sufficiency at a statistically significant annual rate of about 1.5%, representing about 2.9% of the annual average self-sufficiency rate during the study period. This is consistent with the economic logic in terms of increasing the volume of imports at a rate that exceeds 6.3% annually and exceeds the rate of consumption growth (4.43%) over the rate of growth of domestic production (1.73%). The apparent gap increased at an annual statistically significant rate of about 38.5 thousand tons, representing about 7.1% of the annual average gap estimated at around 543.8 thousand tons. It was also found that the most influential factors on the self-sufficiency ratio of poultry meat were the number of imports and the domestic production. Therefore, the strategic stock of poultry meat was estimated at around 621.4 thousand tons, which is sufficient for local consumption for about 7 months, while the value of the food security factor was about 0.58, reflecting the existence of relative food security of poultry meat in the Kingdom. The results of the study also showed the size of the additional loans and investments needed to achieve self-sufficiency and food security for poultry meat in the Kingdom in line with the National Transformation Program and the Kingdom's Vision 2030.